Different manifestations of Thelohanellus nikolskii infection in carp (Cyprinus carpio) - Ćirković M.; Novakov Nikolina; Aleksić Nevenka; Jovanović M.; Ljubojević Dragana; Babić R.; Radosavljević V. (Acta Veterinaria, 2013)
Thelohanellosis is a disease that occurs in all carp categories. The cause is protozoa Thelohanellus nikolskii Achmerov, 1955. It manifests itself in two forms. The first form occurs on the fins in oneyear- old carp fry and the second one occurs on scales in two-yearold, three-year-old and older categories of common carp (Cyprinus carpio). The researches conducted between 2008 and 2012 covered 22 fish ponds, 18 of which are located in Serbia, and 4 in Bosnia and Herzegovina, Republic of Srpska. It has been concluded that both forms of the disease were present in all observed fish ponds. Prevalence of telohanellosis located on the fins ranged between 3% and 30%, and the infection intensity was between 2 and 86 cysts per individual, while in the case of thelohanellosis on scales the values were higher. Changes on the scales were present during April and May, and on the fins during July and August. After determination of morphological characteristics of spores and histopathological characteristics of plasmodia located on the fins and scales, no significant differences were noticed between them. Also, artificial infestation of carp fingerlings for species differentiation was done. Since there are no adequate therapeutic measures, control of thelohanellosis is still based on compliance with basic sanitaryprophylactic measures such as drying of equipment, freezing, mechanical cleaning and disinfection with lime.